Fruit parameters and performance evaluation of mechanical harvester for olive (Olea europaea) fruit - KHDAIR, ADNANI (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during 1999 and 2000 to study optimum time for maximum weight and volume of olive (Olea europaea L.) fruits, detachment force required to remove fmits from branches of 2 cultivars and evaluate performance of a commercially available mechanical olive harvester. The weight and volume obtained optimum values during November and then showed decrease in their values. The detachment force: weight ratio decreased as the season advanced. ’Nabali Rosie’, a larger fruit size cultivur had lower force: weight ratio and was found more suitable for mechanical harvesting by shaking. Evaluation ofmechanical harvester showed that the fmit removal was 42 and 63% for table olive harvest and 60, and 87% for olive oil for ’Nabali’ and ’Nabali Rosie’ respectively.